2006
DOI: 10.1099/jmm.0.46538-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunological alterations during the clinical and recovery phases of experimental swine dysentery

Abstract: The aim of this study was to examine changes in the systemic immune response during the incubation period and following the onset of clinical swine dysentery, including the recovery period. Ten healthy conventional pigs were inoculated with Brachyspira hyodysenteriae. Blood was sampled at pre-inoculation, at days 4 and 14 post-inoculation, during the first 4 days with clinical signs of dysentery and at days 1, 3, 7, 11 and 15 of the recovery period. Eight pigs developed haemorrhagic diarrhoea. Flow-cytometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 55 publications
1
17
1
Order By: Relevance
“…There is further evidence that IFN-␥ is a key molecule in the immune response against viral infection [25], and our results indicate that chronic HBV infection may actually damage TCR␥␦ T cell immune function, as indicated by IFN-␥ production and cytotoxic activity. Some studies in animal models have indicated that the cytotoxic activity of TCR␥␦ T cells is improved during Salmonella infections, but, for some autoimmune diseases in humans, TCR␥␦ T cells remain dysfunctional in order to avoid a hyperstrong immune response [22][23][24][25][26][27][28]. We could not confirm whether the basis for dysfunctional TCR␥␦ T cells in patients with HBV infection is the same as that observed in autoimmune diseases.…”
Section: Table 3 Spearman Correlation Coefficients For Proportions Ocontrasting
confidence: 56%
See 1 more Smart Citation
“…There is further evidence that IFN-␥ is a key molecule in the immune response against viral infection [25], and our results indicate that chronic HBV infection may actually damage TCR␥␦ T cell immune function, as indicated by IFN-␥ production and cytotoxic activity. Some studies in animal models have indicated that the cytotoxic activity of TCR␥␦ T cells is improved during Salmonella infections, but, for some autoimmune diseases in humans, TCR␥␦ T cells remain dysfunctional in order to avoid a hyperstrong immune response [22][23][24][25][26][27][28]. We could not confirm whether the basis for dysfunctional TCR␥␦ T cells in patients with HBV infection is the same as that observed in autoimmune diseases.…”
Section: Table 3 Spearman Correlation Coefficients For Proportions Ocontrasting
confidence: 56%
“…Active TCR␥␦ T cells display nonspecific cytotoxicity against targets without major histocompatibility complex (MHC) restriction [22,23]. Thus, we obtained TCR␥␦ T cells from the peripheral blood by FACS and activated these cells with anti-V␥␦ antibody and rhIL-2.…”
Section: Table 3 Spearman Correlation Coefficients For Proportions Omentioning
confidence: 99%
“…The middle panel shows the system response to the addition of 30 individuals in the Bf_lumen state, representing B. hyodysenteriae , on days 1, 2, and 3. The dynamics observed are in agreement with those seen experimentally in pig infections [52], [53] and generally expected with three distinct phases; i ) the acute inflammation ( days 1–6) marked by an increase in k eDC (not shown) and k Th [Fig. 10(d)], followed by epithelial damage [Fig.…”
Section: Example Application: Explanation Of B Hyodysenteriae Asssupporting
confidence: 89%
“…Parameter values for this demonstration are listed in Table IV and were assigned according to published observations of interactions between bacteria of the Brachyspira genus and immune cells or were fit to cell population dynamics reported in animal infection models [52], [53]. Parameter space was reduced by simplifying assumptions.…”
Section: Example Application: Explanation Of B Hyodysenteriae Assmentioning
confidence: 99%
“…Therefore, these results demonstrated increased cytotoxic potential of γδ T cells in HBV-ACLF. Some other studies also indicated that the cytotoxicity activity of γδ T cells was improved in salmonella infections or other infection diseases [17][18][19][20][21]. In our study, IFN-γ, TNF-α, or IL-17 cytokine production was determined in both the αβ T-cells and the γδ T cells in some HBV-ACLF patients, and the results suggested that the γδ T cells were more powerful in cytokine production than αβ T-cells (Supplementary Figure 2) .…”
Section: Discussionmentioning
confidence: 45%